Rib-oriented thoracoscopic sympathetic surgery for hyperhidrosis: prospective long-term results and quality of life - Nachira, Dania; Meacci, Elisa; Congedo, Maria T.; Petracca-Ciavarella, Leonardo; Zanfrini, Edoardo; Iaffaldano, Amedeo; Vita, Maria L.; Chiappetta, Marco; Griffo, Raffaella; Lococo, Filippo; Margaritora, Stefano (Surgical laparoscopy, endoscopy & percutaneous techniques, 2021)
Background: - The optimal thoracoscopic sympathetic surgery for primary palmar and/or axillary hyperhidrosis (PPAH) is still unclear because of lack of uniform technique and qualitative/quantitative scales for definition of results. The aims of this study were to compare long-term outcomes based on the surgical technique and the level of sympathetic trunk interruption by clipping and to assess postoperative compensatory sweating (CS), patients’ satisfaction, and quality of life (QoL). - Materials and Methods: - Between September 2009 and April 2016, 94 patients who underwent 2-stage bilateral thoracoscopic rib-oriented (R) sympathetic clipping were prospectively followed up through the administration of standardized preoperative and postoperative questionnaires. - Thirty-four (36.2%) patients underwent single-port transaxillary access instead of the standard two 5-mm incisions. The level of sympathetic clipping for PPAH was R3+4(top and bottom); in patients who complained associated facial or plantar hyperhidrosis R2-bottom and R5-top were clipped, respectively. Seventy-five patients completed bilateral surgery. - Results: - There were no significant differences between single-port and biportal video-assisted thoracoscopic surgery in terms of operative times and postoperative results. At a mean follow-up of 72 (SD: 26) months, CS was reported in 42 (56%) patients, severe only in 6 (8%). It was higher in the case of R2-bottom clipping (P=0.03). Thirty-one of 60 (51.6%) patients who had a plantar hyperhidrosis declared an improvement of feet sweating after surgery. Postoperative satisfaction was excellent (86.11% on a 0 to 100 scale) and 95.4% of patients declared an improvement in QoL, which was statistically significant in all evaluated parameters. These results were not related to the level of clipping. - Conclusion: - Thoracoscopic R3 to R4 clipping appears to be a safe and effective treatment for PPAH. Although postoperative CS was common and higher after R2-bottom clipping, this did not seem to affect patients’ satisfaction and improvement in QoL.
Gesehen am 28.07.2021